2008
DOI: 10.1111/j.1750-3841.2008.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fish Myoglobin and Myofibrillar Proteins

Abstract: Interactions between fish myoglobin (Mb) and myofibrillar proteins were investigated in a Mb-natural actomyosin (NAM) model at 4 degrees C. Increases in metmyoglobin (MetMb) formation and the relative content of bound Mb were observed, as were decreases in whiteness and Ca(2+)-ATPase activity (P < 0.05). During the first 6 h of incubation, Mb bound preferably to myosin at domains other than the head portion, as evidenced by measurable ATPase activity. The potential binding of Mb to myosin heads occurred after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
(27 reference statements)
2
15
0
Order By: Relevance
“…This suggested that interactions between MP and SP resulted in increased thermal stability of protein in the system. One of the sarcoplasmic protein, myoglobin, was reported to interact with the tail portion of MHC during incubation at 4 °C for 6 h (Chaijan et al ., ). The interactions were dependent on NaCl concentration and could be occurred at the NaCl concentration used in this study (0.3 m NaCl; Hemung & Chin, ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This suggested that interactions between MP and SP resulted in increased thermal stability of protein in the system. One of the sarcoplasmic protein, myoglobin, was reported to interact with the tail portion of MHC during incubation at 4 °C for 6 h (Chaijan et al ., ). The interactions were dependent on NaCl concentration and could be occurred at the NaCl concentration used in this study (0.3 m NaCl; Hemung & Chin, ).…”
Section: Resultsmentioning
confidence: 97%
“…The discrepancy of the two studies might be partially due to the different protein and moisture contents. In previous study, the oxidation of myogen also resulted in a dark colour (Chaijan et al ., ). Ramirez et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is likely that structural changes in the Mb in the dark muscle were largely responsible for the discoloration of tilapia fillet during iced storage. Under denaturing conditions, hydrophobic residues buried inside the Mb molecule could have been exposed at the surface, causing the aggregation of Mb itself or its adhesion to myofibrillar proteins [47].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for Mb aggregation has been partly characterized; Mb itself tends to self-aggregate (Chow et al, 1989), whereas it has been reported that, in postmortem meat, Mb binds to myofibrillar proteins (Chajian et al, 2008) or reacts with fatty acids (Suman et al, 2007).…”
Section: Resultsmentioning
confidence: 99%